1994
DOI: 10.1111/j.1365-2923.1994.tb02682.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service for medical students

Abstract: The authors describe the problem of impairment of medical students from the point of view of mental health professionals who have directed a large and successful evaluation and referral service for students suffering from a wide array of stress-related and mental disorders. They outline the nature of the impairment problems, the history of the efforts at their medical school to address these problems, and their recent experience in providing mental health services to students who are referred for evaluation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The reality weakness personality trait (which was univariately related to MHPT) is associated with severe personality disorders 20 . Few recent studies have focused upon psychiatric diagnoses and mental health services among medical students and young physicians, although some previous studies have shown that depression and anxiety are the most common diagnoses, followed by a variety of other diagnoses, including substance abuse 1 , 2 , 32 –35 …”
Section: Discussionmentioning
confidence: 99%
“…The reality weakness personality trait (which was univariately related to MHPT) is associated with severe personality disorders 20 . Few recent studies have focused upon psychiatric diagnoses and mental health services among medical students and young physicians, although some previous studies have shown that depression and anxiety are the most common diagnoses, followed by a variety of other diagnoses, including substance abuse 1 , 2 , 32 –35 …”
Section: Discussionmentioning
confidence: 99%
“…Some of these programmes are designed to support impaired students (e.g. Pasnau & Stoessel 1994), or those with specific difficulties such as addiction (Ackerman & Wall 1994). Others are broad based in their approach (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that individuals are better prepared to handle stress and uncertainty when they consider themselves an important member of a group . As medical students are particularly vulnerable to stress, emotional fatigue and burnout, any potentially protective mechanism is of paramount importance …”
Section: Introductionmentioning
confidence: 99%